Women, Media, and Elections : Representation and Marginalization in British Politics - Harmer, Emily (Book collections on Project MUSE., 2021)
Providing a systematic analysis of electoral coverage in newspapers since 1918, this book demonstrates that for women to be effectively represented in the political domain, they must also be effectively represented in the public discussion of politics that takes place in the media.